Scholars in the marketplace : the dilemmas of neo-liberal reform at Makerere University, 1989-2005 - Mamdani, Mahmood, 1946- (Codesria book series., 2007)
Scholars in the Marketplace is a case study of market-based reforms at Uganda's Makerere University. With the World Bank heralding neoliberal reform at Makerere as the model for the transformation of higher education in Africa, it has implications for the whole continent. At the global level, the Makerere case exemplifies the fate of public universities in a market-oriented and capital friendly era. The Makerere reform began in the 1990s and was based on the premise that higher education is more of a private than a public good. Instead of pitting the public against the private, and the state against the market, this book shifts the terms of the debate toward a third alternative than explores different relations between the two. The book distinguishes between privatisation and commercialisation, two processes that drove the Makerere reform. It argues that whereas privatisation (the entry of privately sponsored students) is compatible with a public university where priorities are publicly set, commercialisation (financial and administrative autonomy for each faculty to design a market-responsive curriculum) inevitably leads to a market determination of priorities in a public university. The book warns against commercialisation of public universities as the subversion of public institutions for private purposes.